Modeling mycorrhizal fungi dispersal by the mycophagous swamp wallaby (Wallabia bicolor). Issue 23 (13th October 2020) - Danks, Melissa A.; Simpson, Natalie; Elliott, Todd F.; Paine, C. E. Timothy; Vernes, Karl
Abstract: Despite the importance of mammal‐fungal interactions, tools to estimate the mammal‐assisted dispersal distances of fungi are lacking. Many mammals actively consume fungal fruiting bodies, the spores of which remain viable after passage through their digestive tract. Many of these fungi form symbiotic relationships with trees and provide an array of other key ecosystem functions. We present a flexible, general model to predict the distance a mycophagous mammal would disperse fungal spores. We modeled the probability of spore dispersal by combining animal movement data from GPS telemetry with data on spore gut‐retention time. We test this model using an exemplar generalist mycophagist, the swamp wallaby ( Wallabia bicolor ). We show that swamp wallabies disperse fungal spores hundreds of meters—and occasionally up to 1, 265 m—from the point of consumption, distances that are ecologically significant for many mycorrhizal fungi. In addition to highlighting the ecological importance of swamp wallabies as dispersers of mycorrhizal fungi in eastern Australia, our simple modeling approach provides a novel and effective way of empirically describing spore dispersal by a mycophagous animal. This approach is applicable to the study of other animal‐fungi interactions in other ecosystems. Abstract : Animal‐mediated dispersal facilitates the spread of truffle‐like fungi spores, yet tools to empirically estimate spore dispersal distance are lacking. A simple modeling approach, combining animal movement and gut‐retention data, predicts the distance a mycophagous animal disperses spores. We test the model using the swamp wallaby ( Wallabia bicolor ) and find this mammal disperses ingested spores hundreds of meters from points of ingestion, greater distances than truffle‐like fungi are expected to spread vegetatively. Our study highlights the ecological importance of swamp wallabies as dispersers of mycorrhizal fungi and provides an empirical modeling approach that can be applied to other animal‐fungi interactions.